The Ameliorating Effects of Bushen Huatan Granules and Kunling Wan on Polycystic Ovary Syndrome Induced by Dehydroepiandrosterone in Rats - Xu, Yang; Pan, Chun-Shui; Li, Quan; Zhang, Hao-Lin; Yan, Li; Anwaier, Gulinigaer; Wang, Xiao-Yi; Yan, Lu-Lu; Fan, Jing-Yu; Li, Dong; Han, Jing-Yan (Frontiers in Physiology, 2021)
Aim To investigate the effects of Bushen Huatan Granules (BHG) and Kunling Wan (KW), the two Chinese medicines, on the regulation of polycystic ovary syndrome (PCOS) and their underlying mechanisms. Materials and Methods PCOS rat model was established by subcutaneous injection of dehydroepiandrosterone (DHEA) (6 mg/100 g/day) for 20 days, followed by treatment with BHG (0.75, 1.49, and 2.99 g/kg) or KW (0.46, 0.91, and 1.82 g/kg) by gavage for 4 weeks. Estrous cycle was detected by vaginal smears. Follicles development was assessed by histology. Levels of testosterone and insulin in serum were tested by ELISA. Apoptosis of Granulosa cells (GCs) was evaluated by terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end-labeling staining. Pathways associated with apoptosis were detected with western blot. Pregnancy outcome was also assessed. GCs were pre-treated with 10–5 M testosterone in vitro for 24 h, then incubated with serum from rats receiving BHG (1.49 g/kg) or KW (1.82 g/kg). The parameters concerning apoptosis, mitochondrial function and endoplasmic reticulum stress were assessed. Results Post-treatment with either BHG or KW ameliorated DHEA-induced irregular estrous cycles, follicles development abnormalities, increase of testosterone and insulin in serum, and the apoptosis of GCs. Post-treatment with BHG decreased the expression of cleaved caspase-9/caspase 9, release of cytochrome C from mitochondria, and mitochondria reactive oxygen species production, increased activities of complex I, II, IV of ovarian tissue. Post-treatment with KW decreased the levels of caspase-12, GRP78, C/EBP homologous protein, phosphorylation of IRE-I, x-box-binding protein 1s, as well as phosphorylation of proline-rich receptor-like protein kinase, phosphorylation of eukaryotic translation initiation factor 2α and ATF4 of ovarian tissue and GCs. Both BHG and KW ameliorated pregnancy outcome. Conclusion This study demonstrated BHG or KW as a potential strategy for treatment of PCOS induced by DHEA, and suggested that the beneficial role of the two medicines were mediated by different pathway with the effect of BHG being correlated with the regulation of mitochondria, while the effect of KW being attributable to protection of endoplasmic reticulum stress.